The Use of Subscores in Higher Education: When Is This Useful? - Meijer, Rob R.; Boevé, Anja J.; Tendeiro, Jorge N.; Bosker, Roel J.; Albers, Casper J. (Frontiers in Psychology, 2017)
Assessment in higher education is challenging because teachers face more students, with less contact time as compared to primary and secondary education. Therefore, teachers and management are often interested in efficient ways of giving students diagnostic feedback and providing information on the basis of subscores is one method that is often used in large-scale standardized testing. In this article we discuss some recent psychometric literature that warns against the use of subscores in addition to the use of total scores. We illustrate how the added value of subscores can be evaluated using two college exams: A multiple choice exam and a combined open-ended question and multiple choice exam; these formats are often used in higher education and represent cases in which using subscores may be informative. We discuss the implications of our findings for future classroom evaluation.